The Evaluation of Student’s Knowledge about Climate Change Phenomenon: Gender, Demographic Region, and Student’s Attitudes toward The Environment - Djauharoh, Ainin; Shofiyah, Noly (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to describe students' knowledge about the phenomenon of climate change based on gender and demographic region and describe the effect of environmental attitudes on the level of students' knowledge of the phenomenon of climate change in Indonesia. This research is a quantitative survey type research using a questionnaire as the main instrument in the research. The instrument used was a questionnaire about student’s knowledge of climate change phenomena and students' environmental attitudes. The population in this study was 1080 students taken from various junior high schools in Indonesia. Sampling used a random sampling technique to obtain a total of 302 samples. Because of previous studies were only conducted abroad and in Indonesia many were conducted at the university and high school levels, this research focuses on the junior high school level with the consideration that students have received material about global warming. The results showed that students' knowledge of the phenomenon of climate change in Indonesia was relatively high. It is known that the knowledge level of female students is higher than male students and students who live in villages are higher than students who live in cities. In addition, the level of students' knowledge about climate change is also significantly influenced by students' attitudes towards the environment. This research provides further empirical insight into how teachers should facilitate students' knowledge of the phenomenon of climate change according to gender, demographic region, and attitudes toward the environment.